2015
DOI: 10.7567/jjap.54.07hc08
|View full text |Cite
|
Sign up to set email alerts
|

Closed-crack imaging and scattering behavior analysis using confocal subharmonic phased array

Abstract: To solve the underestimation of closed-crack depth, we have developed an imaging method, subharmonic phased array for crack evaluation (SPACE). However, a single-array SPACE can image only the vicinity of a transmission focal point (TFP) when the TFP is fixed. In this study, we have developed a confocal SPACE that defines multiple TFPs for imaging closed cracks over a wide area. We demonstrated its usefulness by measuring a stress corrosion crack (SCC). Moreover, we proposed a radarlike display that shows sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…32 The SCCs were formed in the heat-affected zones (HAZs) of a weld made of an austenitic stainless steel (SUS304) due to residual stress in hightemperature pressurized water at 280°C, which is almost the same as the environment in actual nuclear reactors. As a consequence, two SCCs were introduced into both HAZs as illustrated in Fig.…”
Section: (A) and 2(d) The Imaging Results Corresponding To Figs 2(mentioning
confidence: 99%
See 1 more Smart Citation
“…32 The SCCs were formed in the heat-affected zones (HAZs) of a weld made of an austenitic stainless steel (SUS304) due to residual stress in hightemperature pressurized water at 280°C, which is almost the same as the environment in actual nuclear reactors. As a consequence, two SCCs were introduced into both HAZs as illustrated in Fig.…”
Section: (A) and 2(d) The Imaging Results Corresponding To Figs 2(mentioning
confidence: 99%
“…On the other hand, the closure of the crack at the root due to the high-temperature environment, which can occur in thermal power plants has been explicitly observed in eddy current testing (ECT). 32 In such a case, it is necessary to apply a nonlinear ultrasonic method to SAW PA, 23,24 such as by using subharmonic waves 3 and/or thermal stress. 10 Furthermore, from a physical viewpoint, the comparison between UT and ECT is useful for clarifying the physical mechanism of crack closure.…”
Section: (A) and 2(d) The Imaging Results Corresponding To Figs 2(mentioning
confidence: 99%
“…In order to evaluate nonlinear behaviour (the production of higher order harmonics), the presence of damage was correlated to higher harmonics. Nonlinear ultrasound phased array and imaging techniques have been assessed by the following authors [30][31][32][33][34]; Ohara et al and Park et al have extensively developed, evaluated and improved the detection of open and closed cracks in metallic structures using a subharmonic phased array, while Potter et al has developed a nonlinear array based on the traditional total focusing method (TFM). These works have not focused on composite material or healing evaluation using these techniques.…”
Section: Non-destructive Testing (Ndt) Of Recovery Processmentioning
confidence: 99%
“…[22][23][24]. Based on that, some studies demonstrated accurate monitoring of fatigue crack growth in metallic samples using nonlinear phased array methods relying on the measurement of the second harmonic [25], the sub-harmonics [26][27][28][29] and the diffuse field energy [30,31]. However, higher harmonic and sub-harmonic generation can be partially or totally related to system/instrumentation nonlinearities, and the acquisition of the diffused field of all array elements is time consuming and requires advanced signal processing [31,32].…”
Section: Introductionmentioning
confidence: 99%